Banking and Currency Legislation, 1932 - Harris, S. E. (Quarterly Journal of Economics, 1932)
Journal Article Banking and Currency Legislation, 1932 Get access S. E. Harris S. E. Harris Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 46, Issue 3, May 1932, Pages 546–557, https://doi.org/10.2307/1883400 Published: 01 May 1932